Can Small Diameter Holes and Low-Density Product Improve Pre-Split Results? - Jim Daley (International Society of Explosives Engineers, 1996)
This case history discusses a pre-split test conducted at BHP Mineralss Navajo Mine in Fruitland, New Mexico. The test was an extension of earlier pre-split testing conducted by Virgil Stachura of the U.S. Bureau of Mines in conjunction with Navajo Mine and WESCO Inc. which tested low-density product in 10.625 diameter holes.